2011
DOI: 10.1007/s00261-011-9791-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric subepithelial masses: evaluation of multidetector CT (multiplanar reconstruction and virtual gastroscopy) versus endoscopic ultrasonography

Abstract: MDCT with MPR and VG is a valuable method for the evaluation of SEMs. Specific MDCT criteria for various SEMs may be helpful in making an accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Most of these EUS findings closely corresponded with those of previous reports [6,16]. On APCT, GISTs usually present with a well-defined margin and homogeneous contrast enhancement [14]. Previous studies have reported that attenuation values of 30–35 HU in pre-contrast imaging and 50–60 HU in post-contrast imaging are helpful in the differential diagnosis of GISTs using APCT [10,18].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Most of these EUS findings closely corresponded with those of previous reports [6,16]. On APCT, GISTs usually present with a well-defined margin and homogeneous contrast enhancement [14]. Previous studies have reported that attenuation values of 30–35 HU in pre-contrast imaging and 50–60 HU in post-contrast imaging are helpful in the differential diagnosis of GISTs using APCT [10,18].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, APCT is expected to play a more relevant role in the diagnosis of gastric SETs in the future. To date, the diagnostic ability of EUS and APCT with respect to gastric SETs has not been adequately compared, with only a few previous studies having reported the accuracy of APCT based on EUS findings as the standard of reference [9,13,14]. This study therefore aimed to compare the diagnostic ability of EUS and APCT and to assess whether they are satisfactory modalities for diagnosing gastric SETs based on surgical histopathology results.…”
Section: Introductionmentioning
confidence: 99%
“…EUS is superior to other imaging modalities (CT, magnetic resonance imaging) in characterizing small (<2 cm) lesions. 8,9 It can accurately distinguish between extrinsic compression of the GI tract and an intramural growth; up to 30% of suspected intramural SELs are in fact extramural in origin (eg, compression from an adjacent organ). 10,11 EUS also permits measurement of lesion size and evaluation of any associated lymphadenopathy for further staging.…”
mentioning
confidence: 99%
“…As it can distinguish various types of SMTs of the stomach, it plays a very important role in determining tumor location and choosing treatment method[ 7 - 9 ]. Studies have found that EUS is better than computed tomography (CT) or magnetic-resonance imaging (MRI) for SMTs < 2 cm[ 10 , 11 ]. The general manifestation of GSTs under EUS is as follows: The tumor originates from the muscularis propria, except for a small part that originates from the muscularis mucosa.…”
Section: Introductionmentioning
confidence: 99%